Analysing the Influence of Industrial Value - Added of Small and Micro-sized Firms on Regional FDI in Indonesia - Celine Canes; Vanessa Aurelia; Juan Phillip Yoel Tanesia; Albert Hasudungan; Erica Lukas (Sekolah Tinggi Manajemen IPMI, 2021)
The role of Foreign Direct Investment (FDI) has only grown in tandem with globalization, as it plays a dual function by improving capital accumulation whilst simultaneously growing total factor yield, which puts it at an advantage over foreign aids and foreign portfolio investments. Using panel data from 34 Indonesian provinces over the 2015 - 2019 period, this research examined the determinants of provincial FDI and its impact on regional economic development in Indonesia. The random effect method with robust standard error was used to regress the model, and the variables found to be positively significant were the ratio of industrial value added for micro sized firms to regional GDP, as well as the growth rate of industrial value added for small sized firms. Our analysis revealed that micro-sized firms tend to have much higher industrial value added compared to small-sized firms, and that these firms tend to cluster in Western Indonesia. The role of the government should be to foster the growth and competitiveness of small and micro-sized firms, especially for regions where the industrial value added is still low. Further study is suggested on the determinants of industrial value added at the provincial level, as well as more comprehensive research on FDI determinants with a larger dataset.